Intrauterine programming of the glucocorticoid-insulin-like growth factor 1 (GC-IGF1) axis mediates glomerulosclerosis in female adult offspring rats induced by prenatal ethanol exposure. (1st September 2019) - He, Hangyuan; Xiong, Ying; Li, Bin; Zhu, Yanan; Chen, Haiyun; Ao, Ying; Wang, Hui
Highlights: Prenatal ethanol exposure (PEE) induced glomerulosclerosis in the female adult offspring rats. PEE-induced adult offspring glomerulosclerosis was originated from fetal kidney dysplasia. Glucocorticoid-insulin-like growth factor 1 (GC-IGF1) intrauterine programming mediates fetal kidney hypoplasia and adult glomerulosclerosis induced by PEE. The glucocorticoid -activation system mediated PEE-induced GC-IGF1 axis programming in the female offspring kidney. Abstract: Prenatal ethanol exposure (PEE) causes intrauterine growth retardation (IUGR), and the occurrence of glomerulosclerosis is closely related to IUGR. This study aimed to confirm the kidney toxic effect of PEE and explore its intrauterine programming mechanism in female offspring. The Wistar female fetuses on gestational day (GD) 20 and the adult offspring at postnatal week 24 were anesthetized and decapitated. The adult offspring kidneys in the PEE group displayed glomerular hyperplasia and glomerulosclerosis. Blood urea nitrogen (BUN) and the BUN / Serum creatinine (Scr) concentration ratio in the PEE group was increased significantly compared to the control group ( P <0.01, P <0.05). Meanwhile, the renal glucocorticoid-activation system was inhibited, whereas the insulin-like growth factor 1 (IGF1) signaling pathway was activated in the female adult offspring of the PEE group. In the fetal kidney of the PEE group, pathological observation showed kidney dysplasia, and the gene expression of the glial-cell-line-derived neurotrophic factor/tyrosine kinase receptor (GDNF/c-Ret) signaling pathway was reduced compared to that of the control group. Moreover, the glucocorticoid-activation system was activated, whereas the IGF1 signaling pathway was inhibited in the fetal kidneys of the PEE group. In conclusion, PEE caused fetal kidney dysplasia and adult glomerulosclerosis in the female offspring rats, and the intrauterine programming alteration of glucocorticoid-insulin-like growth factor 1 (GC-IGF1) axis might be involved in fetal-originated glomerulosclerosis.